Effect of Drying Temperature on the Physical-chemical and Sensorial Properties of Eggplant (Solanum melongena L.) - Guiné, Raquel (2018)
Background: Eggplant is an important crop, being cultivated and consumed in many countries. However, like other vegetables, is highly perishable and has a short shelf life. Objective: The objective of this study was to evaluate the effect of hot air drying on some physical, chemical and sensorial properties of eggplant. Methods: Eggplant samples were dried in convective chambers at constant temperatures of 50, 60, 70 and 80°C. The fresh and dried samples were evaluated for moisture, water activity, vitamin C, total phenolic compounds, antioxidant activity, colour and texture. To complement the study, a sensorial evaluation was made by a consumer panel. Results: The results showed that drying decreased importantly the contents of vitamin C and phenolic compounds as well as antioxidant activity. Moreover, the negative impact was higher for higher drying temperatures. Drying also altered the colour, turning the samples darker. The textural properties were similarly considerably altered by drying, although the temperature did not show significant influence. Regarding the sensorial evaluation, even though it allowed establishing the sensory profiles of the dried samples, it was not possible to clearly distinguish among them, particularly the global appreciation. Conclusion: It was concluded that the drying operation substantially changed the physical, chemical and sensory properties of eggplant. Furthermore, the drying temperature had higher effect on the chemical components and colour and nor so much on the texture.